Análise paleomagnética da Formação Rio Claro no município de Rio Claro (SP) - Pimentel, Giovana Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Rio Claro Formation is a Cenozoic unit deposited on Paleozoic sediments of the Paraná Basin. Located in the geomorphological province of Paulista Peripheral Depression, middle-east of the São Paulo State, the unit is composed of fluvial deposits constrained by topographic and structural features. Some authors proposed ages for the Rio Claro Fm. spanning Pleistocene to Miocene, based on correlations with geomorphological and / or structural events. Available numerical datings places the unit within the earliest Middle Pleistocene. The definition of Rio Claro Fm age is relevant because it is essential to understand the evolution and configuration of the current landscape, as well the associated neotectonic and climatic processes in them. This unit exemplifies the general difficulty of dating continental deposits when there are no materials that can be dated by radiometric methods or key-fossils. In this work paleomagnetism was applied to provide chronological constraints for the Rio Claro Fm. We analyzed 78 samples from two stratigraphic sections, one located in the Mãe Preta and the second along the railroad of Rio Claro city. The magnetic mineralogy revealed the predominance of hematite, which justifies the thermal demagnetization treatment in the laboratory measurements. The magnetoestratigraphy shows the predominance of inverse polarity, with brief periods of normal polarity. The mean direction site calculated was 176.5 / 42.3 with a95 of 3.8 °. The angle of inclination has a rotation of 3.5 ° counterclockwise which seems to be related to the Pitanga Structure old faults reactivation. The calculated palaeomagnetic pole of -86.2 / 9.1 reveals a completely outside paleolongitude that also seems to be influenced by regional tectonism. The paleolitude is coherent and indicates an age between 10 and 20 Ma, positioning the deposition of the Rio Claro Formation in Miocene

A Formação Rio Claro é uma unidade cenozoica depositada sobre rochas paleozoicas da Bacia do Paraná. Localizada na província geomorfológica da Depressão Periférica Paulista, centro-leste do estado de São Paulo, esta unidade é composta por depósitos de origem fluvial delimitados por condicionantes topográficos, litológicos e estruturais. Diversos autores propuseram idades para a Formação Rio Claro baseadas em correlações com eventos de cunhos geomorfológico e/ou estrutural, além de datações absolutas que colocaram a unidade num período de tempo que vai do Mioceno ao Pleistoceno. A definição da idade da Fm. Rio Claro tem sua importância científica por ser essencial ao entendimento da evolução e configuração da paisagem atual e dos processos neotectônicos e climáticos nelas atuantes. Essa unidade exemplifica a dificuldade geral de datar depósitos continentais pela geral ausência de fósseis guias e de materiais apropriados para os métodos radiométricos. Neste trabalho foi aplicado o paleomagnetismo para procurar evidências cronológicas para os depósitos da Fm. Rio Claro. Para tal, foram analisadas 78 amostras distribuídas em duas seções colunares principais, uma na voçoroca do Bairro Mãe Preta e a segunda nas margens da ferrovia da cidade de Rio Claro. A mineralogia magnética revelou o predomínio de hematita justificando a aplicação do método de desmagnetização térmica. A magnetoestratigrafia mostrou o predomínio da polaridade inversa, com breves períodos de polaridade normal. Isso já indica que a Fm. Rio Claro não se depositou durante o campo atual, ou seja, deve ter uma idade mais velha que 780.000 anos. A direção paleomagnética média calculada foi de 176.5/42.3 com um erro associado (a95) de 3.8°. O ângulo de declinação mostra uma rotação de 3.5° no sentido anti-horário e opolo paleomagnético calculado, de 86.2° S / 9.1° E, releva uma...
Keywords: Geologia estratigráfica; Paleomagnetismo; Geomorfologia; Geologia estrutural; Hematita; Rio Claro (SP)